The Effect of Motorcycle Wheels (Original Equipment Manufacturer) Reconditioning Process on Mechanical Properties and Microstructure - Nasution, Ahmad Kafrawi; Alfindo; Sunaryo (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2024)
Wheels are an essential component of a vehicle. Material damage or failure on casting wheel-type wheels is primarily because these wheels receive a reasonably hard impact load due to uneven road conditions or potholes. This condition makes the wheels unable to function normally, and components must be replaced. Given the relatively high cost of replacing wheels, several options are offered to vehicle owners (consumers) to have their wheels reconditioned. This study aims to analyze the effect of the reconditioning process on the mechanical properties and microstructure of the casting wheel material. The sample material is taken from the Original Equipment Manufacturer (OEM) wheel casting wheel in the Disk section for impact testing, Rim for hardness, and microstructure tests. The results are that the reconditioning process affects the mechanical properties and microstructure of the original equipment manufacturer (OEM) alloy wheel material. The decrease in hardness value was 68.86 HBW to 61.59 HBW from the conditions before and after reconditioning. The impact test results where the impact energy absorption is greater after reconditioning is 29.24 J, and the average impact value for wheel specimens after reconditioning is 0.2902 J/mm2. The impact energy value before reconditioning is 7.87 J, and the average impact value is 0.0973 J/mm2. The microstructure obtained is hypereutectic, and the reconditioning process has little effect on the dendritic structure.